Системний аналіз макросередовища підприємств сфери послуг - Васильченко, Олена Олегівна; Vasylchenko, Olena (Запоріжжя : 2023, 2023)
UA: У статті зроблено акцент на актуальність впливу макросередовища на діяльність підприємств сфери послуг. Наголошено на важливості функціонування сфери послуг в економіці країн світу та України. Охарактеризовано структуру сфери послуг. Здійснено аналіз різноманітних підходів до тлумачення економічної категорії “макросередовище”. Охарактеризовано основні фактори макросередовища. EN: In today's conditions, the service sector actually provides all the processes occurring in the macro environment, creating the basis for its successful functioning. However, in turn, she works within this environment, which makes her dependent on its factors, which have both positive and negative effects on her. From this, it becomes clear that both the macro-environment and the sphere of services cannot exist in isolation, and the change of any component in one of these spheres inevitably causes a reaction from the other. It is this symbiosis that determines the need to study the influence of the macro-environment on the processes taking place in the service sector. Conclusions. The sphere of services is a sector of the economy that occupies a leading role in the economy of all countries of the world, it is with its help that the largest part of GDP is formed. The main feature of this sphere is that it is not related to the direct production of material values, but provides all types of activities that contribute to this process. Studying the opinions of scientists regarding the macroenvironment, it became clear that there is currently no single interpretation of this concept. Each of the scientists sees the macroenvironment differently, but some of the concepts described by them have common features. By systematizing them in this way, you can see the idea that appears in each separate vision of this concept, namely that the macro-environment is a system of external factors over which each individual business entity has no leverage, and therefore must fully adapt to their changes for its successful functioning. Conclusions. An enterprise operating in the service sector must take into account not only the factors that it can influence independently, but also the factors of the macro environment in which it operates. Without timely adaptation to changes in these factors, the company can lose its positions, and, on the contrary, when correcting its activities taking them into account, it can achieve stability and significant competitive advantages.
System analysis of the macro-environment of enterprises in the field of services
Keywords: сфера послуг; структура сфери послуг; середовище організації; макросередовище; фактори макросередовища підприємства; the sphere of services; the structure of the sphere of services; the environment of the organization; the macro-environment; the factors of the macro-environment of the enterprise